TRAINING OF PROCESSING OF BANANA STEM CHIPS IN IMRPOVING OF COMMUNITY ECONOMY - Susan Daniel; Seth Miko; Yesni Nopy (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2021)
The fundamental problem lies in the inability and lack of entrepreneurship skills for the community in Takaras Village, Manuhing District, Gunung Mas Regency. Therefore, it is necessary to develop women group who empower family welfare in that area. Community empowerment through training on banana stems as chips as a household business can be a alternative solution. By this activity, it is expected to be able to mobilize all the potential of the community so that they can become capable, skilled, independent, as well as creative to improve their standard of living. Coaching in providing training to PKK household wives is to provide knowledge and skills to the community. The community has the knowledges and skills of entrepreneurship, to produce the stuffs that can improve the economy level of their family.